2017
DOI: 10.4103/0970-0218.205216
|View full text |Cite
|
Sign up to set email alerts
|

Summer temperature and spatial variability of all-cause mortality in Surat city, India

Abstract: Background:Ample information is available on extreme heat associated mortality for few Indian cities, but scant literature is available on effect of temperature on spatial variability of all-cause mortality for coastal cities.Objective:To assess the effect of daily maximum temperature, relative humidity and heat index on spatial variability of all-cause mortality for summer months (March to May) from 2014 to 2015 for the urban population of Surat (coastal) city.Materials and Methods:Retrospective analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
(10 reference statements)
3
11
1
Order By: Relevance
“…There is a significant increase in the risk of all-cause mortality, with maximum temperature rise as evident from other studies (Harlan et al, 2014; Rathi et al, 2017; Rocklov et al, 2014; Son et al, 2012). The high HI values tend to be well associated with mortality from all causes, which is supported by Desai et al and Monteiro et al’s study (Desai et al, 2015b; Monteiro et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…There is a significant increase in the risk of all-cause mortality, with maximum temperature rise as evident from other studies (Harlan et al, 2014; Rathi et al, 2017; Rocklov et al, 2014; Son et al, 2012). The high HI values tend to be well associated with mortality from all causes, which is supported by Desai et al and Monteiro et al’s study (Desai et al, 2015b; Monteiro et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…Because age or cause of death data were not available, all-cause mortality data were analysed as previously done (Desai et al, 2015b; Rathi et al, 2017). This study does not distinguish heat-related mortality due to the unavailability of clear causal deaths.…”
Section: Limitationsmentioning
confidence: 99%
“…However, we did not find significant association with place of residence. It is contradictory with findings from other studies [17,24,25]; so, we assume it is not simply the place of residence, but individual and housing factors that contribute to heat illness. Previous studies have focused only on slum areas without a comparison population.…”
Section: Discussioncontrasting
confidence: 79%
“…The study also concluded the spatial variation of all-cause mortality at zonal level with temperature. [ 1 ] Global public health scenario is changing because of remarkable burden of diseases and mortality due to climate change, especially extreme temperatures. Studies have shown that heat waves are the most significant weather-related cause of mortality throughout the world.…”
mentioning
confidence: 99%